A study on factors influencing junk food consumption behavior among human resource students at UiTM Malacca City Campus / Hazila Fiqa Hassim and Siti Nor Mohamed - Hassim, Hazila Fiqa; Mohamed, Siti Nor (Faculty of Business Management, 2016)
The study of junk food consumption behavior among Human Resource students at UiTM Malacca City Campus is aimed to have an in depth analysis of factors influencing junk food consumption behavior among university students. The research takes up an exploratory approach and used primary data from sample survey conducted on a quota sample to arrive to conclusions. The factors to be investigated in the study were identified from secondary literature. Survey was conducted among a sample of students through distribution of questionnaires. SPSS were being used to analyze the survey data. Female Human Resource students give more respond to the survey about the factors influencing junk food consumption behavior compared to male students. The research indicates that factors like cost (price), convenience, peers influences and advertising are having an influence in making students choose to consume junk foods. The findings of the research lead to the conclusions that the factors influencing junk food consumption behavior among students at UiTM Malacca City Campus was peers influences and advertising.